1998
DOI: 10.1161/01.str.29.3.673
|View full text |Cite
|
Sign up to set email alerts
|

A New Noninvasive Technique for Imaging Atherosclerotic Plaque in the Aortic Arch of Stroke Patients by Transcutaneous Real-Time B-Mode Ultrasonography

Abstract: Background and Purpose-Aortic arch atherosclerotic plaque is a probable source of atheroembolic stroke. Transesophageal echocardiography (TEE) has been used to image the aorta of patients with stroke to identify atherosclerotic plaque. TEE is moderately invasive and does not always visualize plaques present in the distal ascending aorta and proximal aortic arch. Methods-In the current study, transcutaneous B-mode ultrasonography was performed to image the aortic arch through a lateral supraclavicular window, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…TEE is a moderately invasive technique, and a transcutaneous approach has been applied for evaluation of plaque in the aortic arch [18]. Despite improvement in transthoracic ultrasound techniques [19], TEE still gives a more secure visualization of the aortic arch in our hands in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…TEE is a moderately invasive technique, and a transcutaneous approach has been applied for evaluation of plaque in the aortic arch [18]. Despite improvement in transthoracic ultrasound techniques [19], TEE still gives a more secure visualization of the aortic arch in our hands in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic plaque may be visualized with TTE B-mode imaging. 53 Harmonic imaging may add to the accuracy of this technique. 54 …”
Section: Transthoracic Echocardiographymentioning
confidence: 99%
“…46,47 Studies also have shown an association between aortic plaque seen on chest x-ray and the subsequent development of clinical CAD. 48 Examinations of the aorta by B-mode US 49 and TEE 50 have been used as predictors of CAD and cardiovascular risk. 14 Using TEE, the French Aortic Plaque in Stroke group 14,15 found a significantly increased risk of all vascular events for patients who had noncalcified aortic plaques Ͼ4 mm in thickness.…”
Section: Noninvasive Imagingmentioning
confidence: 99%